Multiwavelength observations of EXO 0748-676. I. Reprocessing of X-ray bursts - Hynes, R; Horne, K; O'Brien, K; Haswell, C; Robinson, E; King, A; Charles, P; Pearson, K (2006)
We present high time-resolution multi wavelength observations of X-ray bursts in the low-mass X-ray binary UY Vol. Strong reprocessed signals are present in the ultraviolet and optical, lagged and smeared with respect to the X-rays. The addition of far-ultraviolet coverage for one burst allows much tighter constraints on the temperature and geometry of the reprocessing region than previously possible. A blackbody reprocessing model for this burst suggests a rise in temperatures during the burst from 18,000 to 35,000 K and an emitting area comparable to that expected for the disk and/or irradiated companion star. The lags are consistent with those expected. The single-zone blackbody model cannot reproduce the ratio of optical to ultraviolet flux during the burst, however. The discrepancy seems too large to explain with deviations from a local blackbody spectrum and more likely indicates that a range of reprocessing temperatures are required. Comparable results are derived from other bursts, and in particular the lag and smearing both appear shorter when the companion star is on the near side of the disk as predicted. The burst observed by HSTalso yielded a spectrum of the reprocessed light. It is dominated by continuum, with a spectral shape consistent with the temperatures derived from lightcurve modeling. Taken as a whole, our observations confirm the standard paradigm of prompt reprocessing distributed across the disk and companion star, with the response dominated by a thermalized continuum rather than by emission lines. © 2006. The American Astronomical Society, All rights reserved.